2014
DOI: 10.3340/jkns.2014.55.6.337
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Postural Correction and Subsequent Balloon Inflation in Deformity Correction of Acute Osteoporotic Vertebral Fractures

Abstract: ObjectiveTo determine deformity correction by postural correction and subsequent balloon inflation in acute vertebral compression fractures (OVCFs) and to examine the effect of bone mineral density on deformity correction.MethodsA totol of 50 acute OVCFs received balloon kyphoplasty. Lateral radiographs were taken and analyzed at five different time points : 1) preoperative, 2) after placing the patient in prone hyperextended position, 3) after balloon inflation, 4) after deposition of the cement, and 5) posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Dynamic fracture mobility initially attracted attention because it implied complete corticocancellous disruption and allowed height recovery of the vertebra after postural reduction [ 25 , 26 ]. Liu et al reported that placement of the patient in prone hyperextended position produced a significant reduction of anterior vertebral height by 5.51±2.64 mm, middle vertebral height by 4.35±2.73 mm, and posterior vertebral height by 3.79±3.22 mm [ 27 ]. In turn, these vertebral height changes also aggravate damage to the peri-vertebral wall, thereby increasing the risk of cement leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic fracture mobility initially attracted attention because it implied complete corticocancellous disruption and allowed height recovery of the vertebra after postural reduction [ 25 , 26 ]. Liu et al reported that placement of the patient in prone hyperextended position produced a significant reduction of anterior vertebral height by 5.51±2.64 mm, middle vertebral height by 4.35±2.73 mm, and posterior vertebral height by 3.79±3.22 mm [ 27 ]. In turn, these vertebral height changes also aggravate damage to the peri-vertebral wall, thereby increasing the risk of cement leakage.…”
Section: Discussionmentioning
confidence: 99%
“…The supine position cannot reflect a real operative position. For these reasons, we adopted intraoperative prone cross-table lateral radiographs as a diagnostic tool for dynamic fracture mobility, which was recommended by Cawley et al 23 , 29 , 33 , 34 This positioning technique reduced provoked pain, advanced anterior vertebral height restoration, and supported vertebral deformities correction.…”
Section: Discussionmentioning
confidence: 99%